Estrategias para el mejoramiento de la recuperación de cartera de crédito vencida y castigada del Banco Nacional de Fomento sucursal Balzar - Alcívar Méndez, Flor del Rocío (2012)
The present thesis entitled "strategies for the improvement of the recovery of defeated and punished credit portfolio the Banco Nacional de Fomento Sucursal Balzar, consists in the development of strategies to the aforementioned department that composes the institution as well as its main processes, identify critical areas to generate a possible solution and cope with changes in the environment." It would begin with chapter I which covers the contextual framework of the research or the general knowledge of the institution. Then with chapter II, which covers the contextual framework of the research upon which to be framed in the concepts of various authors such as: Bank, Bank, public and private, credit, lines of credit, plan, strategies, the importance and types of strategies. Chapter III describes the methodology of research, materials and methods that we use as a statistical, analytical, deductive, and inductive, the type of research: Basic, field and bibliographic; as well as also the design research as the determination of objectives, the formulation of the hypothesis and the population and sample to was taken from the Banco Nacional de Fomento portfolio data, applying the formula and giving as result the survey 364 customers. In chapter IV, includes results and discussion the analysis and interpretation of the results of the surveys carried out, detailing the diagnostic swot, the amounts and the lines of credit granted, internal processes of the Department of credit and portfolio and the development of the recovery plan which will favour the liquidity of the entity. Chapter V covers the proposal issued in order that recovery strategies are implemented since the portfolio is very high and with a high degree of difficulty for the recovery of the same. In chapter VI, we have the conclusions and recommendations that maintain and improve the management of the department.